KCNQ2 mutations in childhood nonlesional epilepsy: Variable phenotypes and a novel mutation in a case series - Inn‐Chi Lee; Tung‐Ming Chang; Jao‐Shwann Liang; Shuan‐Yow Li (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Epilepsy caused by a KCNQ2 gene mutation usually manifests as neonatal seizures during the first week of life. The genotypes and phenotypes of KCNQ2 mutations are noteworthy. Methods The KCNQ2 sequencings done were selected from 131 nonconsanguineous pediatric epileptic patients (age range: 2 days to 18 years) with nonlesional epilepsy. Results Seven (5%) index patients had verified KCNQ2 mutations: c.387+1 G>T (splicing), c.1741 C>T (p.Arg581*), c.740 C>T p.(Ser247Leu), c.853 C>A p.(Pro285Thr), c.860 C>T p.(Thr287Ile), c.1294 C>T p.(Arg432Cys), and c.1627 G>A p.(Val543Met). We found, after their paternity had been confirmed, that three patients had de novo p.(Ser247Leu), p.(Pro285Thr), and p.(Thr287Ile) mutations and neonatal‐onset epileptic encephalopathy; however, their frequent seizures remitted after they turned 6 months old. Those with the c.387+1G>T (splicing), (p.Arg581*), and p.(Val543Met) mutations presented with benign familial neonatal convulsions. In addition to their relatives, 14 patients had documented KCNQ2 mutations, and 12 (86%) had neonatal seizures. The seizures of all five patients treated with oxcarbazepine remitted. Conclusion KCNQ2‐related epilepsy led to varied outcomes (from benign to severe) in our patients. KCNQ2 mutations accounted for 13% of patients with seizure onset before 2 months old in our study. KCNQ2 mutations can cause different phenotypes in children. p.(Pro 285Thr) is a novel mutation, and the p.(Pro 285Thr), p.(Ser247Leu), and p.(Thr287Ile) variants can cause neonatal‐onset epileptic encephalopathy.